Examining the Scarcity of Asian America and Pacific Islander Presidents and Chancellors in North American Universities: Implications for Strategic Executive Advancement. Issue 1 (2nd January 2023) - Takamine, Kurt; Jun, Alexander; Collins, Christopher; Ching, Doris
Abstract: The lived experiences of eight Asian American and Pacific Islander (AAPI) university presidents and chancellors in North America revealed the racism and discrimination these Asian academic executives faced and provided counternarratives to dismantle a White normative perspective. While these executive stories were meant to be understood as a unique journey of each academician, common themes and subthemes emerged relating to AAPI academic advancement. The lived experiences of these Asian executives focused on the prevalence of institutional racism, along with the remediation of social injustice through power redistribution to AAPI higher education leaders.